Strategi Masyarakat Mengatasi Investasi Bodong Robot Trading DNA Pro Di Kota Denpasar dan Kota Singaraja - Hetarie, Samuel Christian; Arjawa, I Gst. Pt. Bagus Suka; Kamajaya, Gede (JURNAL ILMIAH SOSIOLOGI: SOROT; Vol 3 No 1 (2023): JISSOROT, 2023)
This research focuses on the rational choices of people in Denpasar City and Singaraja City who are victims of the fraudulent investment of the DNA Pro trading robot. The purpose of this research is to find out the causes of investing in DNA Pro trading robots as the people's choice in Denpasar City and Singaraja City and to find out how the people of Denpasar City and Singaraja City control and control the funds invested in Pro DNA trading robot investments with the theoretical study of James Coleman's Rational Choice. The method used in this study is a qualitative approach with a descriptive-explorative type. The results of this study reveal that there are internal and external factors that influence the people in Denpasar City and Singaraja City in participating in the DNA Pro trading robot investment. This study also shows that the people in Denpasar City and Singaraja City as actors have reasons and goals in participating in investing in the DNA Pro trading robot. Communities participating in these investments can also control the funds they invest by choosing investment packages based on their respective economic capabilities. However, when the investment fraud occurred, the government froze all existing funds in the DNA Pro trading robot investment and the public could not withdraw the funds they had invested. Therefore, a strategy is needed for the community to overcome fraudulent investments that are circulating, such as investing in the DNA Pro trading robot.